Analysis of premixed and non‐premixed co‐injection of volatile gas in an industrial indirect pyrolysis plant. (1st December 2020) - Khodaei, Hassan; Olson, Chris; Nikrityuk, Petr A.
Abstract: Production of raw biochar from the pyrolysis of residual wood and biomass materials has recently been bolstered, in part, due to new indirect slow pyrolysis technologies such as continuous moving bed biochar reactors, rotary kiln reactors, and rotary auger systems. The self‐ignition of wood volatile gas blended with supplement fuel is achievable by adequate mixing of volatiles and stoichiometric air under standard combustion temperatures. In this study, two different CFD simulations were deployed to investigate co‐combustion of a non‐premixed swirl air/propane burner. In particular, one case with pre‐mixed air/pyrolysis gases and one case with non‐premixed air/pyrolysis gases were considered in this work. Pyrolysis gases were produced in an indirect industrial pyrolysis plant taking into consideration the contribution of major volatile components such as CH4, CO2, and CO, and two typical moisture contents predicted using the heat transfer analysis between the combustion chamber and the pyrolysis section. The finite rate model/eddy dissipation model coupled with the realizable k‐epsilon RANS model was used to render turbulence‐chemistry interactions. Validation against experimental data published in the literature and measured in the system demonstrated reasonable agreements. It was shown that the injection of premixed volatile gases and air with high temperature results in higher efficient combustion and better heat transfer rate between the combustion chamber and pyrolysis section rather than the alternative non‐premixed conditions. Due to safety considerations, utilizing a non‐premixed configuration in indirect biochar plant is advised, and further improvements through a pre‐heated excess air system and advanced swirl non‐premixed air/volatile injection nozzles is considered to mitigate the energy deficit in this configuration.